HUBUNGAN KADAR ANTI-MULLERIAN HORMON (AMH) DENGAN SIKLUS HAID TIDAK TERATUR PADA MAHASISWI JURUSAN KEDOKTERAN FAKULTAS KEDOKTERAN DAN ILMU â ILMU KESEHATAN UNIVERSITAS JENDERAL SOEDIRMAN - ., Mustofa; A, Setyawan; UA, Pekerti (MANDALA of Health, 2013)
Background : Anti-Mullerian Hormone (AMH), also known as MÃ¼llerian inhibiting substance, is a protein hormone to follicle development. Menstrual cycle that occurs outside the normal state or the interval pattern of menstruation that is less than 21 or more than 35 days with normal uterine bleeding time span of less than 3 or more than 7 days is irregular menstrual cycles. Objective : This study aimed to know the association AMH level and irregularly menstrual cycle at student of medical faculty and health sciences Jenderal Soedirman University. Method : This study was done at 26 subjects, use Analytic observational method with cross-sectional approach. Subjects was chosen by consecutive sampling technic and adapted to inclusion and exclusion criteria. Subjects asked to fasting 12 hours and then collect their blood until reach 10 cc. Data analysis used chi square then followed to coefficient contingency test with alt lambda test. Result : The level of AMH in irregular menstrual cycle group is 8.87 ng/ml. It shows a higher yield than regular menstruation group (4.28 ng/ml). The result of this study there is have association between AMH level and irregularly menstrual cycle at student of medical faculty and health sciences Jenderal Soedirman University. p 0,001 and 95 % CI = 1,828 â 83,767 that showed there was moderate association. Conclusion : There is strong association between AMH level and irregularly menstrual cycle at student of medical faculty and health sciences General Soedirman University, The study shows a very strong association that abnormal of serum AMH will have irregular menstrual cycles, whereas AMH levels are relatively normal will have regular menstrual cycles